Evaluation of Pegylated Liposomal Doxorubicin Dose on the Adverse Drug Event Profile and Outcomes in Treatment of Recurrent Endometrial Cancer. Issue 2 (1st February 2013) - Julius, Justin M.; Tanyi, Janos L.; Nogueras-Gonzalez, Graciela M.; Watkins, Jack L.; Coleman, Robert L.; Wolf, Judith K.; Smith, Judith A.
Abstract : Objective: This study aims to determine factors that may increase the likelihood of adverse drug events (ADEs) in patients with recurrent endometrial cancer treated with pegylated liposomal doxorubicin (PLD) as well as this agent's impact on clinical outcomes. Methods: The treatment records of patients with endometrial cancer who received PLD at The University of Texas, MD Anderson Cancer Center, from 1996 to 2006 were reviewed. Patient demographics, PLD dose, ADEs, use of supportive care interventions, disease progression, and survival were extracted. Logistical regression analysis was used to identify factors that were associated with higher incidence of ADEs and that influenced survival. Results: A total of 60 patients with recurrent endometrial cancer were identified who experienced 122 ADEs. The most commonly reported ADEs were nausea (18.9%), palmar-plantar erythrodysesthesia (PPE; 16.4%), muscle weakness (12.3%), mucositis (10.7%), and peripheral neuropathy (9.8%). Seventeen patients (28%) required a dose reduction because of ADEs. However, only 5 (8.3%) patients discontinued therapy because of toxicity. Cooling mechanisms were used in 19 patients to prevent PPE, although 9 of these patients still experienced PPE. Treatment with 6 or more cycles of PLD was associated with increased incidence of neutropenia ( P = 0.045), peripheral neuropathy ( P = 0.004), and PPE ( P < 0.001). No differences in progression-free survival or time to progression were found between the doses of PLD; however, there was an assessable trend toward increased survival with doses of 40 mg/m 2 . Conclusions: Although there was no association with dose level and ADEs, more cycles received increased the incidence of toxicities, including PPE and neuropathy. There was no association between different doses of PLD and progression-free survival or time to progression.